Emerging use of everolimus in the treatment of neuroendocrine tumors - Gajate P; Martínez-Sáez O; Alonso-Gordoa T; Grande E (Cancer Management and Research, 2017)
Pablo Gajate, Olga Martínez-Sáez, Teresa Alonso-Gordoa, Enrique Grande Medical Oncology Department, Ramon y Cajal University Hospital, Madrid, Spain Abstract: Neuroendocrine tumors (NETs) consist of a diverse family of malignancies, which are derived from neuroendocrine cells, most commonly originating from the gastroenteropancreatic (GEP) tract or the bronchopulmonary system. In general, NETs are more indolent than epithelial tumors, with median survival rates of longer than 30 months. The upregulation of mTOR pathway has been shown to play a pivotal role in NET pathogenesis. Inhibition of mTOR protein with everolimus represents a progress in the treatment of advanced NETs. Everolimus has shown a significant improvement in progression-free survival (PFS) among patients with pancreatic NETs (pNETs) and nonfunctional GEP and lung NETs in the Phase III RAD001 in Advanced Neuroendocrine Tumors (RADIANT)-3 and RADIANT-4 studies, respectively. In addition, the combination of everolimus with octreotide showed a clinically significant improvement versus octreotide alone in functional NETs in the RADIANT-2 trial. These studies led to the US Food and Drug Administration (FDA) and European Medical Agency (EMA) approval of everolimus. Safety profile of everolimus is generally acceptable. The most common adverse events are stomatitis, diarrhea, rash and fatigue. There is a growing range of novel treatment options in the setting of NETs, but there are no data comparing the activity of different treatment strategies. Thus, treatment decisions are based on different aspects, such as clinical course, patient symptomatology, primary tumor site, tumor functionality, rate of progression and burden of disease. Further research is required to clarify the treatment sequencing to achieve the maximum prolongation in survival and maintenance of quality of life. Future research should concentrate on identification of predictive biomarkers for benefit from different therapies, and studies should also include quality of life as an important measurement in this disease. Keywords: everolimus, mTOR inhibitor, pancreatic neuroendocrine tumors, gastrointestinal neuroendocrine tumors, systemic treatment